SHORT-TERM OUTCOMES OF USING CUSTOM 3D PRINTED BASE PLATES IN REVERSE SHOULDER ARTHROPLASTY FOR PATIENTS WITH GLENOID CAVITY DEFECTS - Makarov, Vasyl; Korzh, Mykola (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
Objective. To conduct a retrospective analysis of the short-term clinical and radiographic outcomes of reverse total shoulder arthroplasty using custom glenoid base plates in patients with glenoid cavity defects. Methods. We retrospectively studied the surgical outcomes of 10 patients with defects of the glenoid cavity who underwent reverse total shoulder arthroplasty using individual glenoid base plates. The average follow-up period postsurgery was (2.6 ± 1.6) years. The mean age of the patients was (62.4 ± 5.6) years, including 7 women (70 %) and 3 men (30 %). Two patients (one woman and one man) underwent RTSA on both shoulders, resulting in a total of 12 RTSA procedures performed on 10 patients. All patients underwent shoulder joint imaging using spiral computed tomography, modeling of the individual base plate implant for the glenoid part of the endoprosthesis, and fabrication of the implant using 3D printing with titanium powder. The function of the shoulder joint was evaluated using the Constant-Murley Shoulder Score (CMS). Results. The mean cortical index was 0.38 ± 0.06. Lateralization and distalization angles were measured at 80° ± 5.6° and 55° ± 8.2°, respectively. The average active range of motion for external rotation was 60° ± 5.5°, flexion and elevation of the upper limb at the shoulder joint (including the scapula) was 135° ± 8.4°, internal rotation was 85° ± 3.4°, and abduction of the shoulder joint (including the scapula) was 145° ± 10.2°. The mean score on the CMS scale was 85. Conclusion. The retrospective analysis demonstrates a significant reduction or complete absence of pain syndrome along with improved functional outcomes in patients after RTSA with glenoid cavity defects when using custom base plates for the glenoid part of the reverse shoulder endoprosthesis.